2021
DOI: 10.1042/bsr20203336
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of tumor mutation burden and immune microenvironment in gastric cancer

Abstract: Tumor mutation burden (TMB) was a promising marker for immunotherapy. We aimed to investigate the prognostic role of TMB and its relationship with immune cells infiltration in gastric cancer (GC). We analyzed the mutation landscape of all GC cases and TMB of each GC patient was calculated and patients were divided into TMB-high and TMB-low group. Differentially expressed genes (DEGs) between the two groups were identified and pathway analysis was performed. The immune cells infiltration in each GC patient was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 47 publications
4
9
0
Order By: Relevance
“…MUC16, which encodes the cancer antigen CA-125, was shown to be strongly associated with higher TMB and favorable survival outcomes in GC patients (30). Our result illustrated that GC patients with high TMB had a higher survival rate than those with low TMB, which was consistent with the result of Zhao et al (31), Yu et al (32) and Wang et al (33). Besides, higher TMB was associated with late T and N stages.…”
Section: Discussionsupporting
confidence: 91%
“…MUC16, which encodes the cancer antigen CA-125, was shown to be strongly associated with higher TMB and favorable survival outcomes in GC patients (30). Our result illustrated that GC patients with high TMB had a higher survival rate than those with low TMB, which was consistent with the result of Zhao et al (31), Yu et al (32) and Wang et al (33). Besides, higher TMB was associated with late T and N stages.…”
Section: Discussionsupporting
confidence: 91%
“…Maurer’s study found that compared with normal tissues adjacent to cancer, the expression of ICAM-1 (intercellular adhesion molecular-1) in CRC tissues was significantly increased and positively correlated with the infiltration of inflammatory cells in the tumor microenvironment. The results of in vitro culture experiments show that the high expression of ICAM-1 depends on the increased dose of IFN-Îł and IL-1β( Maurer et al, 1998 ; Xiang et al, 2001 ), For the high-risk cohort: KEGG analysis shows that the neuroactive ligand receptor interaction is mainly signaling pathway, that consistent with recent research ( Yu et al, 2021 ) ( Supplementary Figure 8 ). Moreover, CG Score was identified as an independent prognosis predictor for patients with CRC.…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, the activation of protein anabolism is important to high-grade cancers because proteins are required for cell division during proliferation and against cancer-associated cachexia and malnutrition [36]. Studies have reported that neuroactive ligand receptor interactions are involved in tumor immune infiltration and metastasis [37][38][39]. Therefore, these pathway analysis results may contribute to the comprehensive illumination of the hidden pathogenesis of IMPA.…”
Section: Discussionmentioning
confidence: 97%